Effects of daily creative writing practice at school on the cognitive development of children from disadvantaged socio-economic backgrounds - Hubert, Cédric; Bonnardel, Nathalie; Frey, Aline (Thinking skills and creativity, 2025)
•Creativity is a key skill to face the challenges of tomorrow.•Creativity can be learn and improved at school through creative writing workshops.•The improvement of creativity can transfer to other skills such as verbal fluency.•This improvement also reinforces imagination and emotional stability personality traits. Creativity has become an essential skill in our complex, globalized and digital society. The question is whether it is possible to develop this skill at school. The aim of the present study was to analyze the effects of daily 20-minute creative writing workshops for primary school children, from low socio-economic backgrounds, on the development of their creative thinking skills and other more general skills. This longitudinal experiment involved a total of 161 participants in grades 2 to 5, who were assigned each year to either a creative writing group, a choral singing group, or a passive control group that did not participate in either workshop. Students were assessed at the beginning and end of each year on a range of creative, language and graphomotor skills, as well as on five personality traits. Results showed a significant advantage for the creative writing group in the development of verbal divergent thinking, imagination and emotional stability than the other groups, as well as an improvement in their verbal fluency. Spelling and graphomotor skills were not improved. These results highlight the fact that creativity may be a skill that can be trained at school, at least in a modality-specific way (in this case, verbal). Additionally, this improvement in creativity could transfer to other, more general skills. Overall, this study has the great advantage of showing, in the context of a longitudinal ecological study, the concrete benefits of training in creative writing, which seems promising for the future development of creativity at school.